Making urbanizing deltas more resilient by design - Meyer, Han (International Planning History Society Proceedings, 2016)
Talking about ‘resilience’ and ‘adaptability’ seems to be a new fashion in the world of architecture and urbanism. Many people use these terms without explaining what they mean. Both terms are often used in combination with, and even as synonym of, terms like ‘incremental’ and ‘bottom-up’ and as an alternative of large scale ‘top-down’ interventions by the state. But it is far more than a new fashion; the use of these terms indicates a process of fundamental transition of paradigms in planning and design. This paradigm-change is related to a farewell of modernist and reductionist ideas and approaches in science, engineering and design. For a long time these modernist ideas were dominating, suggesting that it is possible to know and understand the world (the social world as well as the physical world) completely, and that, based on this knowledge, it is possible to plan and control the development of the world completely. A large range of events contributed to the rising idea that it is impossible to know, predict and control the world completely: the social revolts of the 1960s, the messages of the Club of Rome in the 1970s, the concerns with climate change since the 1990s and many more. They contributed to an increasing awareness that systems in nature as well in society are complex, and that the developments of these complex systems are non-linear, with a basically uncertain future ( Scheffer 2009; Mitchell 2009). This uncertain future means that we have to take into account that disturbances can happen suddenly, unexpected, and also that external conditions can change substantially. Moreover, the size and scale of these disturbances and changes are unknown. The situation and the challenges in urbanizing deltas are interesting examples in the current discussion. In a recent report, composed by TU Delft and the Delta Alliance, commissioned by the Dutch Ministry of Foreign Affairs for the preparation of the UN-Habitat-III conference, the authors argue that delta regions are the most promising regions of the world, but in the same time these regions are the most vulnerable zones, were floods, draught, salinization and pollution result in major risks for millions of people, for economic development and for the environment (Meyer, Peters 2016).